Platelet activating factor receptor antagonists improve the efficacy of experimental chemo- and radiotherapy - Ildefonso Alves da Silva Junior; Luciana Nogueira de Sousa Andrade; Sonia Jancar; Roger Chammas (Clinics, 2018)
Platelet activating factor is a lipid mediator of inflammation, and in recent decades, it has emerged as an important factor in tumor outcomes. Platelet activating factor acts by specific binding to its receptor, which is present in both tumor cells and cells that infiltrate tumors. Pro-tumorigenic effects of platelet activating factor receptor in tumors includes promotion of tumor cell proliferation, production of survival signals, migration of vascular cells and formation of new vessels and stimulation of dendritic cells and macrophages suppressor phenotype. In experimental models, blocking of platelet activating factor receptor reduced tumor growth and increased animal survival. During chemotherapy and radiotherapy, tumor cells that survive treatment undergo accelerated proliferation, a phenomenon known as tumor cell repopulation. Work from our group and others showed that these treatments induce overproduction of platelet activating factor-like molecules and increase expression of its receptor in tumor cells. In this scenario, antagonists of platelet activating factor markedly reduced tumor repopulation. Here, we note that combining chemo- and radiotherapy with platelet activating factor antagonists could be a promising strategy for cancer treatment.